New year, new ambitions! - Sheba Nakacubo Gitta (Journal of Interventional Epidemiology and Public Health)
Welcome to volume 8 of the Journal of Interventional Epidemiology and Public Health (JIEPH). It is a delight to pen this editorial in the sixth year of JIEPH´s uninterrupted publication and as the African Field Epidemiology Network (AFENET) —our publisher — celebrates 20 years.